Popular Culture, Social Media, and The Politics Of Identity - Kiraz, Ersel (Aydin Adnan Menderes University, 2025)
Popular Culture, Social Media, and The Politics of Identity" explores the intersection of popular culture, social media, and identity politics in contemporary society. The book examines how individuals construct and express their identities, the role of social media in this process, and how popular culture shapes these expressions. The authors provide a theoretical and practical framework to understand how digital platforms influence social, cultural, and political identities. It delves into the impact of social media content, memes, trends, and user interactions on the dynamics of identity politics. The book highlights how popular culture products circulating on social media redefine categories such as globalization, gender, race, and class. By addressing both academic perspectives and everyday social media phenomena, the book appeals to a wide audience. It serves as a vital reference for scholars in sociology, media studies, cultural studies, and communication. The authors adopt a critical lens, encouraging readers to consider the profound effects of social media on identity construction at both individual and societal levels. This book is an essential resource for understanding the evolving nature of identity politics in a digitalized world. It offers thought-provoking insights into the transformative power of social media and popular culture in shaping contemporary identities.

"Popular Culture, Social Media, and The Politics of Identity" çağdaş toplumlarda popüler kültürün, sosyal medyanın ve kimlik politikalarının kesişim noktalarını inceleyen kapsamlı bir çalışmadır. Kitap, bireylerin kimliklerini nasıl ifade ettiklerini, sosyal medyanın bu süreçteki rolünü ve popüler kültür ürünlerinin bu ifadeleri nasıl şekillendirdiğini ele almaktadır. Yazar modern dünyada dijital platformların bireylerin sosyal, kültürel ve politik kimliklerini nasıl etkilediğine dair teorik ve pratik bir çerçeve sunar. Kitap, sosyal medya içeriklerinin, memlerin, trendlerin ve kullanıcıların bu içeriklerle etkileşimlerinin, kimlik politikalarının dinamiklerini nasıl değiştirdiğini ayrıntılı bir şekilde analiz etmektedir. Çalışma özellikle, sosyal medya üzerinden yayılan popüler kültür ürünlerinin küreselleşme, toplumsal cinsiyet, ırk ve sınıf gibi kimlik kategorilerini nasıl yeniden tanımladığını vurgulamakta. Kitap, hem akademik bir temel sunması hem de günlük hayatta karşılaşılan sosyal medya fenomenlerini ele alması nedeniyle geniş bir okuyucu kitlesine hitap etmektedir. Sosyoloji, medya çalışmaları, kültürel çalışmalar ve iletişim alanlarında çalışanlar için önemli bir referans kaynağıdır. Yazar sosyal medyanın kimlik inşası üzerindeki etkilerini analiz ederken eleştirel bir yaklaşım benimseyerek okuyuculara hem bireysel hem de toplumsal düzeyde düşündürücü bir perspektif sunuyor
Popular Culture, Social Media, and The Politics Of Identity
Keywords: Journalism Studies; Gazetecilik Çalışmaları [EN] Communication and Media Studies (Other); İletişim ve Medya Çalışmaları (Diğer)